Is irisin really a neuroendocrine (f)actor? (Annals of Medical Research, 2024)
Irisin was identified as a peptide hormone in 2012. The most important known physiological effect of irisin is that it activates uncoupling protein 1 and converts white adipose tissue to brown adipose tissue. Due to this effect of irisin on adipose tissue, it was thought that it may be closely related to obesity, feeding behavior and energy expenditure, and interest in research in this direction has increased. Later studies revealed that irisin, beyond its known effects, also influences the reproductive, nervous, cardiovascular, and excretory systems. Recent studies have determined that irisin has anti-oxidant, anti-inflammatory and anti-apoptotic properties, and it has been reported that pathologies such as obesity, endocrine and metabolic diseases, Alzheimer's disease, chronic kidney disease, cardiovascular diseases, atherosclerosis and cancer may be associated with changes irisin levels. The fact that irisin is expressed in different tissues other than muscle and fat tissue and exhibits autocrine and endocrine functions, as well as being expressed in different regions of the brain and participating in neuroendocrine processes in these regions, brings to mind that irisin may be a new neuroendocrine factor. In this review, we present information that will constitute evidence that irisin is a real neuroendocrine factor.
Keywords: Irisin; Food intake; Obesity; Energy balance